Evaluating the Impact of Simulated Patients on Knowledge, Skills and Attitudes of Laypeople Following a Basic First Aid Course: Protocol for a Cluster-Randomized Controlled Trial (International Journal of First Aid Education)
Background: Teaching first aid to laypeople is a cost-effective way to improve public health. However, it is currently unclear what the most effective ways are to teaching first aid. It has already been shown that simulated patients have an added value in teaching emergency care to healthcare professionals. This paper describes the protocol for a cluster-randomized controlled trial that will investigate the influence of using a simulated patient during basic first aid training for laypeople on their knowledge, skills and self-efficacy. Hypothesis: The null hypothesis of this research is that the use of simulated patients during basic first aid training does not result in a statistically significant change in knowledge, skills and self-efficacy concerning the first aid topics for which a simulated patient is used. The alternative is that knowledge, skills and self-efficacy will be influenced by using simulated patients during training. Methods: This study will be a cluster-randomized controlled trial, that will take place from September 2018 to June 2020. The study population will consist of employees from several organisations taking a three day first aid certification course with the Belgian Red Cross. The organisations requesting a first aid course will be randomised in receiving a course with or without simulated patient. The simulated patient will only be used for the topics “first aid for burns” and “first aid for stroke” in the intervention group. The participants will complete a questionnaire to measure their knowledge and self-efficacy, and complete a practical skills test after the course testing these first aid topics. To test whether the retention of first aid knowledge and self-efficacy is influenced by using a simulated patient during a certification course, participants following a refresher course one year after the certification course will complete a follow-up questionnaire. Conclusion: This cluster-randomized controlled trial will be, to our knowledge, the first to investigate the added value of simulated patients during first aid courses for laypeople.